Tinjauan Faktor-Faktor Penyebab Terjadinya Kerusakan Dokumen Rekam Medis Rawat Inap Di Rumah Sakit Putri Hijau Medan - Khairani; Khairannisa Harefa (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda, 2022)
Medical Record is a file containing records and documents regarding patient identity, examination, treatment, actions and other services for patients at health care facilities. The factors that affect archive damage can be divided into two, namely intrinsic factors which are the cause of damage originating from the archive object itself, for example the quality of paper and the influence of ink. extrinsic factors are the causes of damage that come from external factors of archive objects, such as physical, biological and chemical environmental factors. cross-sectional approach, that is, each research subject is only observed once and measurements are made on the status of the character or variable of the subject at the time of examination. Intrinsic factors which include paper, ink and adhesive with the amount of damage to medical record documents caused by ink with a total of 89 (29.5%). Extrinsic factors include physical, biological and chemical factors with 72 (23.9%) damage caused by fungi. The conclusion is that the biggest damage is caused by intrinsic factors, namely chemical damage as many as 89 (29.5%) medical record documents